Strategi Promosi Public Relations Pondok Pesantren Jami’atul Qurro’ Palembang dalam Menarik Minat Calon Santri Baru Tahun 2025 - Hanifah Ummi Ramadhan; Hepi Riza Zein; Umi Rojiati (MAN 4 Kota Pekanbaru, 2025)
Jami’atul Qurro’ Islamic Boarding School Palembang has experienced a steady increase in new student enrollment over recent years, from 131 students in 2022/2023 to 221 in 2023/2024, and 289 in 2024/2025. However, in the 2025/2026 academic year, the number of applicants declined to 266 students. This decrease serves as an important indicator that requires further examination, especially regarding the reach and impact of the pesantren’s promotional strategies. This study uses a descriptive qualitative method through interviews, observations, and documentation with nine informants: one public relations officer, six students, and two parents. The analysis applies the promotion mix theory, which includes advertising, personal selling, sales promotion, public relations, and direct marketing. The findings show that the effectiveness of Public Relations strategies lies in their focus on building the institution’s image, trust, and moral credibility. The pesantren’s promotional success is influenced by program quality, leadership reputation, community participation, and the ability to present religious values in a compelling and relevant way.